Analisis Permintaan Ikan (Studi Kasus: Desa Semparuk Kecamatan Semparuk) - Muslimin; Harmoko; Muslimah (Politeknik Negeri Sambas, 2021)
The purpose of this research is to analyze the factors affecting the demand for fish in the Semparuk Sub-district. The samples in this study were the fish traders who settled and traveled in Semparuk village which amounted to 15 merchants, and the community as a consumer of fish as many as 60 respondents. Data analysis used statistical calculations with data processing techniques using software SPSS 25. The results showed that fish demand in Semparuk village was simultaneously influenced by price, income, and taste. The results of the data analysis in multiple linear regression resulted in an Adjusted R Square value of 0.824 meaning that variable prices (X1), consumer tastes (X2), and consumer income (X3) affected fish demand (Y) in Semparuk Village by 82.4 %. The remaining 17.6 % was influenced by other factors not included in the study.